Metal-free, brønsted acid-catalyzed formal [3+2] annulation of quinone monoacetals with 2-naphthols - Jacob, Anu; Roy, Tony; Kaicharla, Trinadh; Biju, Akkattu T. (Journal of Organic Chemistry, 2017)
An operationally simple and metal-free cross-coupling of quinone monoacetals (QMAs) with 2-naphthols catalyzed by triflic acid is reported. This formal [3+2] annulation allowed the synthesis of diverse naphtho[2,1-b]benzofuranderivatives in moderate to good yields. Preliminary mechanistic studies reveal the initial nucleophilic substitution of QMAs with 2-naphthols in preference to the mixed acetal formation and subsequent [3,3] sigmatropic rearrangement.